2020
DOI: 10.32479/ijeep.8509
|View full text |Cite
|
Sign up to set email alerts
|

Development of Energy Cooperation Between Russia and China

Abstract: The research analyses the question of to what extent the focus on state projects between Russia and China is based on the Russian desire to switch from an economy that is dependent on natural resources. Through the analysis of existing capabilities of the Russian companies to propose opportunities for innovative and technological projects that can be used in the long run. At the same time, the research will focus on energy trends and their presence in Russian and Chinese energy markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The relationship between the ownership structure and the market value of listed commercial banks in China is also studied ( Lukin, 2019 ; Ni, 2019 ). It is concluded that, the United States should seek more control to strengthen their influence over Chinese listed commercial banks ( An et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the ownership structure and the market value of listed commercial banks in China is also studied ( Lukin, 2019 ; Ni, 2019 ). It is concluded that, the United States should seek more control to strengthen their influence over Chinese listed commercial banks ( An et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fuel energy plays a leading role in the Russian economy and in the life of its society (An, J., Dorofeev, M., Zhu, S., 2020). It is important to study the national characteristics of the oil market (Mikhaylov, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite government`s attempts to build up and diversify energy capacities, the last ten years have seen little change (Nyangarika et al, 2019a;Nyangarika et al, 2019b;Ang, 2007;Ang, 2009). By 2021, without the introduction of new energy capacities, the country will again face energy deficiency problem (Gardner et al, 1993;An et al, 2020). The situation is aggravated by the need for a substantial reduction in the coal-based power plants that produce the vast majority of electricity by 2030, in accordance with the Paris Climate Agreement signed by South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%